Effects of Pro/Prebiotics Alone over Pro/Prebiotics Combined with Conventional Antibiotic Therapy to Treat Bacterial Vaginosis: A Systematic Review. (21st April 2022) - Afifirad, Roghayeh; Darb Emamie, Amir; Golmoradi Zadeh, Rezvan; Asadollahi, Parisa; Ghanavati, Roya; Darbandi, Atieh
Abstract : Background . Bacterial vaginosis (BV), caused by an imbalance in the vaginal microbiota, can be treated and prevented by probiotics. Pregnant women with BV can experience premature labor and spontaneous abortions. Probiotics and prebiotics promote the proliferation of beneficial microorganisms, alter the composition of the vaginal microbiota, and prevent intravaginal infections in postmenopausal women. In addition to reducing infection symptoms, pre/probiotics can also help prevent vaginal infections. Materials and Methods . A systematic review was conducted on studies from 2010 to 2020 to determine the efficacy of pre/probiotics on the treatment of BV in pregnant and nonpregnant women. The databases Medline, Scopus, Embase, and Google Scholar were systematically searched using the following keywords: "bacterial vaginosis, " "probiotics, " "prebiotics, " and "synbiotics." Results . A total of 1, 871 articles were found in the initial search, and 24 clinical trials were considered eligible. In studies comparing the effects of pre/probiotics and placebos with or without antibiotic therapy in patients with BV, significant differences in clinical outcomes were observed. Probiotics reduced the levels of IL-1 β and IL-6, as well as the overall Nugent score and Amsel's criteria for restitution of a balanced vaginal microbiota. In addition, probiotics can reduce the vaginal colonization of Group B streptococci among pregnant women. In subjects treated with probiotics, BV cure rates were higher than those in subjects treated with antibiotics. There were no additional adverse events. Conclusion . Pre/probiotic regimens, when used for BV treatment, are usually safe and can exhibit long-term and short-term benefits. In order to prove the benefits of pre/probiotics in BV treatment, additional high-quality research is required.